2021
DOI: 10.2196/28392
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of a Digital Nutrition Platform on Cholesterol Levels in Users With Dyslipidemia: Longitudinal Study

Abstract: Background A strong association exists between consuming a healthy diet and lowering cholesterol levels among individuals with high cholesterol. However, implementing and sustaining a healthy diet in the real world is a major challenge. Digital technologies are at the forefront of changing dietary behavior on a massive scale, as they can reach broad populations. There is a lack of evidence that has examined the benefit of a digital nutrition intervention, especially one that incorporates nutrition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…People would potentially experience metabolic syndrome along with the aging process [43]. Besides, people who suffering dyslipidemia were likely in the older ages and men gendered [44]. A study mentioned that hypercholesterolemia was more common in men instead of women [45].…”
Section: Resultsmentioning
confidence: 99%
“…People would potentially experience metabolic syndrome along with the aging process [43]. Besides, people who suffering dyslipidemia were likely in the older ages and men gendered [44]. A study mentioned that hypercholesterolemia was more common in men instead of women [45].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on the effectiveness of nutrition-only platforms. In one, the effect of a digital nutritional tracking and meal planning platform on lipid markers in individuals with dyslipidemia was assessed, showing improvement in all parameters [ 41 ]. In the second study, a mixture of online and offline engagement was used, with participants who underwent the complete prevention program showing improved cholesterol levels [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The platform also allows users to use SNAP benefits to purchase foods online. Previous research on Foodsmart found improvements in clinical metrics, such as weight, lipid levels, and hemoglobin A 1c , among users with obesity, dyslipidemia, and diabetes, respectively, suggesting clinical benefits of the platform [14][15][16][17].…”
Section: Introductionmentioning
confidence: 93%